Analisis Penokohan Pada Naskah Drama Seni Karya Ahmad Muslih Navis (Kajian Psikologi Sastra) - Putri, Selvia Dwi Erwanda; Arifin, Syaiful; Indrahastuti, Tri (Universitas Mulawarman, 2018)
Psychological studies are very necessary to understand the human psyche. Therefore, it is important to do research on the drama script Seni by Ahmad Muslih Navis. This study aims to describe the characterizations and psychological conflicts in the art drama script by Ahmad Muslih Navis experienced by the main character with Sigmund Freud's theory. The data are in the form of text excerpts that describe the psychology of the main character and the psychological conflict in the drama script. Data collection techniques were carried out in three stages, namely note-taking techniques, reading techniques and interview techniques. The method used in this research is descriptive method, a study that begins with the selection and determination of data, researching according to the formulation of the problem. The instrument in this study was the researcher himself using data cards and interview guides. The focus of this research is to describe the characterization of the main character and the psychological conflicts experienced by the main character of Sigmund Freud, namely, the id, ego, and superego. The results of data analysis in this study that were influenced by id were unyielding, confident, clever in seducing, and compassionate. While the ego-influenced characterizations are succumbing, confident, forward thinking, brave and wise. While the characterizations that are influenced by the superego are attention and discipline. The results of the research on psychological conflicts that are influenced by the id are disappointment, anger and worry. Meanwhile, Rian's ego-influenced psychological conflicts are disappointment, anger, and worry. While the psychic conflict that is influenced by the superego is regret.